2005
DOI: 10.1074/jbc.m410291200
|View full text |Cite
|
Sign up to set email alerts
|

Domain V of β2-Glycoprotein I Binds Factor XI/XIa and Is Cleaved at Lys317-Thr318

Abstract: The fifth domain (DV) of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…They also demonstrated that factor XIa proteolytically cleaved β2GPI at Lys317 -Thr318 of domain V. Thus, factor XIa cleavage of β2GPI in vivo during thrombus formation may accelerate factor XI activation by decreasing the inhibitory effect of β2GPI. 241 In another report, the same group showed that, when both β2GPI and anti-β2GPI were incubated with factor XI, anti-β2GPI potentiated the ability of β2GPI to inhibit the activation of factor XI, and, thus, anti-β2GPI could be considered as a factor that inhibits coagulation. 242…”
Section: The Role Of Apl and Their Respective Antigens In Activatimentioning
confidence: 96%
“…They also demonstrated that factor XIa proteolytically cleaved β2GPI at Lys317 -Thr318 of domain V. Thus, factor XIa cleavage of β2GPI in vivo during thrombus formation may accelerate factor XI activation by decreasing the inhibitory effect of β2GPI. 241 In another report, the same group showed that, when both β2GPI and anti-β2GPI were incubated with factor XI, anti-β2GPI potentiated the ability of β2GPI to inhibit the activation of factor XI, and, thus, anti-β2GPI could be considered as a factor that inhibits coagulation. 242…”
Section: The Role Of Apl and Their Respective Antigens In Activatimentioning
confidence: 96%
“…Because of the high affinity of ␤ 2 GPI for anionic phospholipids, it was thought that ␤ 2 GPI, by inhibition of the contact phase activation of coagulation, could play a role in maintaining the hemostatic balance. [15][16][17] Furthermore, it has been suggested that ␤ 2 GPI is involved in platelet prothrombinase activity and ADP-mediated platelet aggregation. 18,19 ␤ 2 GPI binds liposomes and microparticles via an interaction with phosphatidylserine, and it also is involved in the clearance of these negatively charged cellular fragments in mice.…”
mentioning
confidence: 99%
“…Cleavage can occur at Lys 317 -Thr 318 (11) by plasmin (12) and factor XIa (FXIa) (13). Domain V can bind to thrombin (14), anionic phospholipids (9), FXI (13), heparin (15), apolipoprotein E receptor 2 (16), and GPIb␣ (17,18).…”
mentioning
confidence: 99%